Cyclic di-GMP Is Integrated Into a Hierarchal Quorum Sensing Network Regulating Antimicrobial Production and Biofilm Formation in Roseobacter Clade Member Rhodobacterales Strain Y4I - Armes, April C.; Buchan, Alison (Frontiers in Marine Science, 2021)
Microbial biofilms associated with marine particulate organic matter carry out transformations that influence local and regional biogeochemical cycles. Early microbial colonizers are often hypothesized to “set the stage” for biofilm structure, dynamics, and function via N-acyl homoserine lactone (AHL)-mediated quorum sensing (QS). Production of AHLs, as well as antimicrobials, contributes to the colonization success of members of the Roseobacter clade. One member of this group of abundant marine bacteria, Rhodobacterales sp. Y4I, possesses two QS systems, phaRI (QS1) and pgaRI (QS2). Here, we characterize mutants in both QS systems to provide genetic evidence that the two systems work in hierarchical fashion to coordinate production of the antimicrobial indigoidine as well as biofilm formation. A mutation in pgaR (QS2) results in decreased expression of genes encoding both QS systems as well as those governing the biosynthesis of indigoidine. In contrast, mutations in QS1 did not significantly influence gene expression of QS2. Addition of exogenous AHLs to QS1 and QS2 mutants led to partial restoration of indigoidine production (45–60% of WT) for QS1 but not QS2. Mutational disruptions of QS1 had a more pronounced effect on biofilm development than those in QS2. Finally, we demonstrate that c-di-GMP levels are altered in QS and indigoidine biosynthesis Y4I mutants. Together, these results indicate that pgaRI (QS2) is at the top of a regulatory hierarchy governing indigoidine biosynthesis and that the global regulatory metabolite, c-di-GMP, is likely integrated into the QS circuitry of this strain. These findings provide mechanistic understanding of physiological processes that are important in elucidating factors driving competitiveness of Roseobacters in nature.